Broadband Compact Substrate-Independent Textile Wearable Antenna for Simultaneous Near- and Far-Field Wireless Power Transmission - Mahmoud Wagih; Abiodun Komolafe; Alex S. Weddell; Steve Beeby (IEEE Open Journal of Antennas and Propagation, 2022)
Despite an increasing interest in wearable wireless power transmission (WPT), until now, wearable antennas have been unable to simultaneously harvest from near-field resonant and far-field radiative WPT. Here, a dual-port antenna is proposed, integrating an inductive coil with a broadband monopole for near- and far-field wearable WPT. The coil acts simultaneously as a High Frequency (HF) near-field power receiver and an Ultra-High Frequency (UHF) resonator, enabling the miniaturization of the enclosed broadband monopole, both fabricated using all-textile conductors. On-body, the antenna maintains a 10 dB return loss over a measured 135% fractional bandwidth while maintaining compactness ( $0.312× 0.312λ ^{2}$ ). The antenna is substrate-independent and is demonstrated on two textile substrates with different dielectric properties and thicknesses. In far-field mode, the rectenna maintains over 40% efficiency from sub-1 $μ \text{W}$ /cm2 power densities. In the near-field, a WPT efficiency up to 80% can be achieved. The simulated Specific Absorption Rate (SAR) shows up to 40 and 20 dBm power reception for HF and UHF operation, respectively, without exceeding the 1.7 W/kg limit. The far-field wearable rectenna is demonstrated powering a Bluetooth Low Energy node using a BQ25504 DC-DC converter from a best-in-class low power density of 0.88 and $0.55~μ \text{W}$ /cm2 on-body and in-space, respectively.